The electronic structures and magnetic properties of mixed-valence Fe-based metal–organic VNU-15 frameworks: a theoretical study from linear response DFT+U calculations. Issue 57 (18th September 2020) - Dang, Diem Thi-Xuan; Dong, Hieu Cao; Kawazoe, Yoshiyuki; Kuo, Jer-Lai; Nguyen-Manh, Duc
Abstract : The effects of DMA + cation orientation on the electronic structures and magnetic properties of the metal–organic framework VNU-15 are investigated, and VNU-15 is proved to be a prospective material for photocatalytic applications. Abstract : The crystal symmetries, electronic structures, and magnetic properties of metal–organic VNU-15 frameworks (VNU = Vietnam National University) were investigated using density functional calculations (DFT) with an on-site Coulomb repulsion approximation, U eff, of 4.30 eV, determined via the linear response method. Two different orientations of dimethylammonium (DMA + ) cations in VNU-15 were investigated. Antiferromagnetic configurations were predicted to be the ground states, with Fe ions in high-spin states for both phases. Furthermore, VNU-15 had intrinsic semiconductor electronic behavior with a small band gap of about 1.20 eV. The change in the orientation of DMA + led to changes in the dispersion of the band structure, the band gap, and the Fe contributions to the valence band and conduction band. A fascinating feature was found involving exchange of oxidation numbers between two adjacent Fe atoms in the two phases. Our results revealed that VNU-15 has strong oxidation activity and predicted the important role of an anisotropic effect on the hole and electron effective masses. The findings presented that the electronic and magnetic properties could be controlled via hydrogen bonds and proved VNU-15 to be a prospective material for photocatalytic applications.